M-learning: Changing Roles of Instructors and Learners - Abdullah, Muhammad Ridhuan Tony Lim; Azelin, Mohamed Noor (Internationaljournal.org, 2010)
Mobile learning or m-learning or wireless learning as the name implies means that learning takes place while in a mobile environment. Mobile in this paper is interpreted as an environment which allows the learner the luxury of mobility, and has several unique characteristics. However this new entry in learning concept certainly has some pedagogical issues. One of them would be the instructors’ and the learners’ role. M-learning envisions that learners have the freedom of getting educated whilst in a non-conventional classroom, and hence, the lessons are accessible anywhere at anytime. In a conventional classroom, the instructor and a group of learners would meet at a designated time and place to interact. All these have to change and a new set of expectations have to be considered. Obviously learners as well as instructors who are interested in m-learning may be unable to attend a traditional classroom and thus would be attracted to the characteristics of m-learning since the latter encompasses and integrates all the features as well as the limitations of eLearning; web-based learning as well as wireless learning or virtual learning. When mobile technologies are combined and armed with sound instructional design approaches, m-learning lessons have a huge advantage when compared to traditional classroom bounded lessons and instructions. This paper discusses the role of the instructors and learners in m-learning, as this type of learning has great potential to be the learning practices of the future.